Insentif Pajak Memoderasi Pengaruh Book-Tax Differences Terhadap Trading Volume Activity - Septiani, Rinda; Tjaraka, Heru (E-Jurnal Akuntansi; Vol 32 No 2 (2022), 2022)
This study aims to obtain empirical evidence on whether book-tax differences (BTD) have a negative effect on trading volume activity (TVA) and whether tax incentives (INST) moderate this effect. The population is companies that are included in the Kompas 100 Index listed on the IDX during the period 2019 and 2020. The sample technique used is purposive sampling with research data of 93 observations. The analysis used in this research is multiple linear regression analysis and Moderated Regression Analysis (MRA). The results show that BTD has a negative effect on TVA. INST in this study does not moderate the effect of BTD on TVA, but INST acts as a predictor variable, meaning that tax incentives have a positive effect on TVA. Keywords : Book-Tax Differences; Trading Volume Activity; Tax Incentives.